PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA NON-FISIK TERHADAP KEPUASAN KERJA KARYAWAN PT. NATIONAL AIRCREW MANAGEMENT - Ratu Inge Rahmaizzaty; Nuridin (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
Purpose to analyze leadership style and non-physical work environment on job satisfaction of employees of PT. National Aircrew Management. This research is included in the category of causal associative research using a quantitative approach. The research population amounted to 48 people, the sampling technique used a saturated sample, all members of the population were used as samples totaling 48 employees at PT. National Aircrew Management. The research method uses simultaneous and partially linear regression analysis. The results of the study indicate that in simultaneous or partially ways, leadership style and non-physical work environment had a positive and significant effect on the Job Satisfaction of PT. National Aircrew Management.